2011
DOI: 10.1007/s12185-011-0928-2
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of peripherally inserted central venous catheters for children with cancer requiring long-term venous access

Abstract: Long-term venous access is essential when treating malignant diseases. We reviewed our experience with peripherally inserted central venous catheters (PICC) in children suffering from various malignancies with regard to catheter life, reasons for removal, and complications. Ninety-three PICCs were inserted in 78 children. Median catheter life was 162 days (range 6-575 days) with a total of 16,266 catheter days. Seventy-five PICCs (80.6%) had been placed until the elective removal or patients' death, whereas 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 17 publications
0
50
2
4
Order By: Relevance
“…In some studies, PICC was indicated for prolonged infusion of intravenous fluids, total parenteral nutrition, antineoplastic agents, antibiotics and blood products. (21,23) Others proposed that it be used according to the treatment protocol (23) and, for the sake a more assertive choice, the professionals should take into account the patient's needs and opinions, as well as the length of the treatment, according to the pre-established protocol. (25) Studies analyzed also show that, when indicating PICC, the professional should consider the patient's type of cancer, (23,25) for example solid or hematological, although they did not mention how to make this decision based on tumor differentiation.…”
Section: Indication For Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, PICC was indicated for prolonged infusion of intravenous fluids, total parenteral nutrition, antineoplastic agents, antibiotics and blood products. (21,23) Others proposed that it be used according to the treatment protocol (23) and, for the sake a more assertive choice, the professionals should take into account the patient's needs and opinions, as well as the length of the treatment, according to the pre-established protocol. (25) Studies analyzed also show that, when indicating PICC, the professional should consider the patient's type of cancer, (23,25) for example solid or hematological, although they did not mention how to make this decision based on tumor differentiation.…”
Section: Indication For Insertionmentioning
confidence: 99%
“…In six studies (21,23,(25)(26)(27)(28) , the physician was mentioned as the most qualified professional for the in-…”
Section: Indication For Insertionmentioning
confidence: 99%
“…Un 13,9% de los 237 CCIP estudiados por Ahn DH et al (17) padecieron una infección relacionada con el catéter, así como en otro estudio, donde hubo 28 casos de infecciones sistémicas y 6 de infección del sitio de salida del catéter de los 93 CCIP estudiados (18) , siendo éstas unas cifras elevadas.…”
Section: Complicaciones Más Frecuentes Infeccionesunclassified
“…Dos de los estudios revisados, presentaron algún paciente con esta complicación: un solo caso, en uno de los estudios (18) y 3, en otro (30) . El protocolo enfermero del Hospital Universitario Ramón y Cajal sobre los CCIP afirma que entre los cuidados de dichos catéteres, se encuentra la vigilancia de aparición de flebitis, la cual deberá realizarse valorando su grado según la escala visual de valoración de flebitis o escala de Maddox (37,38) .…”
Section: Flebitisunclassified
See 1 more Smart Citation